The Pengaruh Multimedia Interaktif Pada Materi Fungsi Komposisi Terhadap Hasil Belajar Siswa Kelas X - Glorya Fransisca Petrus Ly; Damianus Dao Samo; Irna Karlina Sensiana Blegur (FKIP Universitas Mataram, 2023)
The purpose of this study to find out the impact of using interactive multimedia on learning outcomes, especially on function composition subject matter at SMA Negeri 4 Kupang. This research is a quantitative study using 2x2 factorial design: (multimedia class vs non-multimedia class) x (man vs woman).Samples of this study are 28 students from X IPA 3 as the experimental class and 28 students from X IPA 1 as the control class. The research stage starts with the solving of pretest questions, followed by learning activities for the control and experimental classes, and then concludes with the solving of posttest questions. The results show that the use of interactive multimedia has an impact on learning outcomes as demonstrated by an average increase in control class learning outcomes of 36.25 with a moderate N-gain category, whereas the average increase in experimental class learning outcomes was 49.31 with a high N-gain category. The results of the data analysis calculations using a two-way ANOVA shows that there is no interaction between learning methods vs gender indicated by the significance value is 0,413 > 0,05, furthermore the gender effect test shows the significance value is 0,821 > 0,05 means there is no gender effect to student learning outcomes. Lastly, the effect test of experimental class vs control class (learning methods) shows the impact of interactive multimedia on learning outcomes indicated by the score of significance value 0,000 < 0,05